2021
DOI: 10.3892/etm.2021.10871
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-98-5p inhibits human mesangial cell proliferation and TNF-α and IL‑6 secretion by targeting BTB and CNC homology 1

Abstract: MicroRNA (miR)-98-5p has been reported to be involved in the development of lupus nephritis (LN); however, its specific role in LN remains unclear. The present study aimed to investigate the effect of miR-98-5p on human mesangial cell proliferation and the secretion of TNF-α and IL-6. Reverse transcription-quantitative PCR (RT-qPCR) and western blotting were used to analyze the level of gene and protein expression, respectively. Cellular proliferation was assessed using a Cell Counting Kit-8 (CCK-8) assay. ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…IgG anti-dsDNA also drive the expansion of MCs through microRNAs, which are short non-coding RNAs that act as guide molecules in RNA silencing by inducing mRNA degradation or blocking protein translation (73). Research has demonstrated that diverse miRNAs are downregulated in LN induced by anti-dsDNA antibodies and could inhibit MCs' proliferation through multiple signaling pathways, including miR-10a, miR-16, miR-124, miR-133, miR-155, miR-98-5p, miR-146b-5p, and hsa−miR−371−5p (74)(75)(76)(77)(78)(79)(80)(81). Further, some miRNAs exert positive regulatory effects on the proliferation of MCs.…”
Section: Excessive Proliferation Of Mcs In Lnmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG anti-dsDNA also drive the expansion of MCs through microRNAs, which are short non-coding RNAs that act as guide molecules in RNA silencing by inducing mRNA degradation or blocking protein translation (73). Research has demonstrated that diverse miRNAs are downregulated in LN induced by anti-dsDNA antibodies and could inhibit MCs' proliferation through multiple signaling pathways, including miR-10a, miR-16, miR-124, miR-133, miR-155, miR-98-5p, miR-146b-5p, and hsa−miR−371−5p (74)(75)(76)(77)(78)(79)(80)(81). Further, some miRNAs exert positive regulatory effects on the proliferation of MCs.…”
Section: Excessive Proliferation Of Mcs In Lnmentioning
confidence: 99%
“…MiR-146b, miR-124, and miR-203 attenuate the inflammatory response of MCs by inhibiting the expression levels of TNF receptor-associated factor 6 (TRAF6) in LN ( 74 , 75 , 107 , 108 ). MiR-98-5p inhibits the secretion of TNF-α and IL-6 by targeting BACH1 in human MCs ( 80 ). Blocking hsa-miR-127-3p could promote the expression of JAK1 and leads to the excessive activation of the IFN-I signaling pathway in LN ( 109 ).…”
Section: Pathologic Mcs Shape Tissue-resident Immunity In Lnmentioning
confidence: 99%
“…Numerous reviews and preclinical and clinical studies have established and discussed the critical roles of various miRNAs in the development, prognosis, and therapies of LN (Dominguez-Gutierrez et al, 2014;Habibi et al, 2016;Li et al, 2017;Trinh et al, 2017;Zhu et al, 2017;Xu et al, 2018;Ye et al, 2018;Feng et al, 2019;Liu et al, 2019;Qi et al, 2020;Shao et al, 2020;Sun et al, 2020;Abdul-Maksoud et al, 2021;Du et al, 2021;Perez-Hernandez et al, 2021;So et al, 2021;Xu et al, 2021;Zhang et al, 2021). There has been much research and review on the role of miRNAs in LN over the last decade, and several wellknown miRNAs have been linked to the development and progression of LN (Table 1).…”
Section: Micrornas In Lupus Nephritismentioning
confidence: 99%
“…Inflammatory pathways, and that changes in the expression of these miRNAs may be linked to inflammation in LN (Feng et al, 2019;Shao et al, 2020;Du et al, 2021). The critical role of macrophages in inflammatory processes has been well established.…”
Section: Micrornas In Lupus Nephritismentioning
confidence: 99%
See 1 more Smart Citation